PROBLEMS AND SOLUTIONS: INDIAN DIACHRONIC CORPORA - Nozimjon Bobojon ugli Ataboev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The following paper informs about the theoretical data regarding the achievements of English corpus linguistics and the problems of Indian corpus application, creation and multilingualism.